1987
DOI: 10.1095/biolreprod36.1.211
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis as the Mode of Uterine Epithelial Cell Death during Embryo Implantation in Mice and Rats1

Abstract: An ultrastructural study of mouse and rat embryo implantation sites was undertaken to determine whether the uterine luminal epithelial cells surrounding the blastocyst exhibited the morphologic characteristics of apoptotic or necrotic cell death. In both species the epithelial cells exhibited all of the characteristics of apoptosis, including surface blebbing, shrinkage and fragmentation of the cells, condensation of chromatin, and indentation and fragmentation of nuclei. Cytoplasmic organelles remained morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
1
4

Year Published

1992
1992
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(132 citation statements)
references
References 0 publications
4
123
1
4
Order By: Relevance
“…However, unlike previous observations in Klf5 null mice, 5 these retained epithelial layers in the Rac1 null implantation chamber is not due to a reduced Cox2 expression. Because the disintegration of epithelial cells lining the implantation chamber is due to apoptosis in response to the invading blastocyst during normal pregnancy, 14 our findings suggested an intrinsic defect of Rac1 null epithelium undergoing apoptotic cell death after embryo-uterine attachment, highlighting the necessity of epithelial integrity for the initiation and progression of implantation. In fact, it has been reported that Rac1 is required for apoptotic cell clearance in bronchial epithelial cells and cell death in mammary gland epithelium.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, unlike previous observations in Klf5 null mice, 5 these retained epithelial layers in the Rac1 null implantation chamber is not due to a reduced Cox2 expression. Because the disintegration of epithelial cells lining the implantation chamber is due to apoptosis in response to the invading blastocyst during normal pregnancy, 14 our findings suggested an intrinsic defect of Rac1 null epithelium undergoing apoptotic cell death after embryo-uterine attachment, highlighting the necessity of epithelial integrity for the initiation and progression of implantation. In fact, it has been reported that Rac1 is required for apoptotic cell clearance in bronchial epithelial cells and cell death in mammary gland epithelium.…”
Section: Discussionmentioning
confidence: 68%
“…14 There is early evidence that Caspase 3 is an executor of uterine epithelial apoptotic death and loss of Klf5 in mice leads to impaired epithelial cell elimination at postimplantation. 5,15 However, it remained largely elusive regarding the underlying mechanisms governing luminal epithelial cell death after blastocyst-uterus attachment.…”
mentioning
confidence: 99%
“…Cell death, especially apoptosis, of endometrial epithelial cells occurs in implantation sites not only in mice (43), rats (44), and hamsters (45), but also in humans (3,46). Embryo-induced apoptosis of epithelial cells is an important mechanism for invading the luminal epithelium and breaching the epithelial barrier; the immediate consequence is that the trophoectoderm come in direct contact with the basement membrane and, then, stromal invasion can proceed (3).…”
Section: Discussionmentioning
confidence: 99%
“…One developmental process likely to contribute such high levels of extracellular AMP is cell death (Pearson and Gordon, 1979;Gordon, 1986;Papadimitriou et al, 1991). This process has been described in the uterine epithelium (El-Shershaby and Hinchliffe, 1975;Parr and Parr, 1987), primary decidua (Welsh and Enders, 1987;Parr and Parr, 19891, and secondary decidua (Welsh and Enders, 1985;Katz and Abrahamsohn, 1987) during implantation chamber morphogenesis in rodents. Adenosine production by 5'-NT would, by this model, accompany the progression of cell death a t the uterine-embryo interface.…”
Section: Transmural Asymmetry Of Adenosine Concentration Across the Amentioning
confidence: 93%